Cyclical Inclusive Growth Model of the European Union - E. V. Sapir; A. D. Vasilchenko (Vestnik MGIMO-Universiteta)
This article analyzes the distinctive features of the contemporary cyclical inclusive growth model within the European Union (EU). As an integration entity, the EU contends with a series of internal challenges that impede its development, arising from the divergent economic interests of member states and the uneven distribution of the costs and benefits of the 'twin transition' in the context of Europe’s declining global competitiveness. Exploring the nuances of inclusive growth in the EU, particularly the role of citizen participation in societal progress, offers a valuable framework for understanding the social and economic contradictions both within and between member states. The study commences with a critical review of existing definitions of inclusive growth, laying the groundwork for an in-depth analysis of the EU model.The research employs quantitative methods to compare EU member states using the UNCTAD Inclusive Growth Index and additional indicators of social and economic development and well-being. It also evaluates the outcomes of the 'Europe 2020' strategy, which aimed to establish inclusive growth targets for the EU by 2020. The findings reveal that the highest levels of inclusive growth are concentrated in northern and continental European countries, whereas Central and Eastern Europe (CEE) exhibit significantly lower levels. The analysis further uncovers key contradictions, such as the tension between reducing socio-economic inequality and promoting economic growth, the generational conflict over the ‘green economy,’ and the misalignment of interests between smaller and larger EU economies.Despite the initiatives under the 'Europe 2020' strategy, the study observes a shift in the priorities of EU citizens concerning inclusive growth. The research identifies fundamental characteristics of the EU's inclusive growth model, marked by a cycle of emerging and resolving social and economic contradictions at the Union level. A notable aspect of this model is the increasing complexity and multiplicity of contradictions, alongside a growing emphasis on subjective well-being and the fulfillment of intangible individual needs. The insights derived from this analysis have practical implications for developing inclusive growth support measures within the Eurasian Economic Union (EAEU) and can aid in defining priorities and mechanisms for the social and economic policies of EAEU member states.